The Clinicopathological Features of Gastric Hyperplastic Polyps with Neoplastic Transformations: A Suggestion of Indication for Endoscopic Polypectomy - Han, A-Reum (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2009)
BACKGROUND/AIMS: Although gastric hyperplastic polyps are usually considered as benign lesions, a low risk of carcinomatous conversion is currently recognized. We aimed to identify the characteristics of hyperplastic polyps undergoing neoplastic transformation. METHODS: A total of 269 gastric hyperplastic polyps from 216 patients removed by endoscopic polypectomy (EP) or surgical resection were enrolled in this study, and their endoscopic pictures and pathology slides were reviewed. RESULTS: Neoplastic transformation was detected on forceps biopsy specimen in 11 cases. However, the pathology findings from the EP or surgical specimen revealed neoplastic transformation in 14 cases (5.2%; 4 with dysplasia and 10 with adenocarcinoma). No significant difference was found between hyperplastic polyps with and without neoplastic transformation in age, sex, location, number of polyps or gross appearance. However, neoplastic transformations were more frequently found in gastric hyperplastic polyps >1 cm than in polyps ≤1 cm (12 of 143; 8.4% vs. 2 of 126; 1.6%) (p=0.013). CONCLUSIONS: Neoplastic transformations were more frequently found in gastric hyperplastic polyps >1 cm. Therefore, EP should be considered for gastric hyperplastic polyps >1 cm for the accurate diagnosis and definitive treatment.